A study to Assess the Effectiveness of Mindful Meditation on Health and Academic Adjustment Problem Faced by Nursing Students in Selected Colleges of Pune City - Arsha Sarangm1 , Laxmi Kharatm1 , Shubham Talot1 , Sonopant Joshi2 , Ranjana Chavan3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Stress is one of the common problem among students of higher education institutes, it affects healthand academic performance as well. Mindful meditation is one of the useful strategy to reduce stress andimproves health and academic performance among young population. The objective of the study is assessthe effectiveness of mindful meditation on health and academic adjustment problems among 1st year B ScNursing students in selected nursing colleges of Pune city. The research design adopted for this study preexperimental, pre-test post-test design. The study was conducted at selected nursing schools of Pune. Total60 students selected by purposive sampling. The data collected were analysed by descriptive and inferentialstatistics. The result showed that there are multiple health problems student faces during their first year ofcollege life. The stress which occurs in early academic life causes low academic performances. Mindfulmeditation found effective on health and academic performances during early academic life hence collegeshould exercise mindful meditation during their induction and orientation period.